From Critical Theory to Critical Hermeneutics - Øjvind Larsen (Nordicum-Mediterraneum, 2014)
From their beginning in the 1930s, critical theory and the Frankfurt school had their focus on a critique of disturbed social relations in western society dominated by totalitarian political regimes like Stalinism, Fascism, Nazism, and by capitalism as an oppressive and destructive economic system and culture. Now, 80 years later, this has all become history and thus it is time to leave the concept of critical theory behind us, and instead bring the concept of critique to a broader theoretical framework like hermeneutics. This allows the possibility of retaining the theoretical intentions of the old Frankfurt school and at the same time there will be no boundaries by specific dominant theoretical perspectives. In this paper, such a framework for a critical hermeneutics is discussed on the basis of Weber’s, Gadamer’s, and Habermas’ theories on hermeneutics within the social sciences.